Profile of clindamycin phosphate 1.2%/benzoyl peroxide 3.75% aqueous gel for the treatment of acne vulgaris - Nguyen, Tuyet A (Clin Cosmet Investig Dermatol, 2015)
Acne vulgaris is a common and chronic skin disease, and is a frequent source of morbidity for affected patients. Treatment of acne vulgaris is often difficult due to the multifactorial nature of this disease. Combination therapy, such as that containing clindamycin and benzoyl peroxide, has become the standard of care. Several fixed formulations of clindamycin 1% and benzoyl peroxide of varying concentrations are available and have been used with considerable success. The major limitation is irritation and dryness from higher concentrations of benzoyl peroxide, and a combination providing optimal efficacy and tolerability has yet to be determined. Recently, a clindamycin and benzoyl peroxide 3.75% fixed combination formulation was developed. Studies have suggested that this formulation may be a safe and effective treatment regimen for patients with acne vulgaris. Here, we provide a brief review of acne pathogenesis, benzoyl peroxide and clindamycin, and profile a new Clindamycin-BP 3.75% fixed combination gel for the treatment of moderate-to-severe acne vulgaris.